Seasonal Flu A Scare (Homoeopathy for All, 2023)
Seasonal influenza is an acute  respiratory infection caused by  influenza viruses which circulate in  all parts of the world. It represents a  year-round disease burden. However,  influenza can cause severe illness or  death, particularly among high risk  groups including the very young,  the elderly, pregnant women, health  workers and those with serious  medical conditions. This article  provides an overview of the aetiology,  diagnosis, and appropriate general  & homoeopathic management of  Seasonal flu.
Keywords: diagnosis; Seasonal flu